COVID-19 and chronic kidney disease: what should we know about ACE/ACE-2 ratio? - Vizcarra-Vizcarra, Cristhian Adolfo (2020)
Viral infection with the SARS-CoV-2 coronavirus produces a disease called COVID–19, characterized by a severe acute respiratory syndrome that can progress to multiple organ failure and death. Patients who have this entity commonly present various comorbidities, among which chronic kidney disease stands out, which could be related to severe infection. High levels of ACE / ACE – 2 ratio plays an important role in the pathophysiology of chronic kidney disease and in different cardiovascular diseases, predisposing these patients to develop infection with a poor prognosis. Up to 46% of hemodialysis patients with COVID are asymptomatic, although some present with fever, cough, and dyspnea, and it is common to observe gastrointestinal symptoms that must be taken into account when evaluating this group of patients in dialysis units.